1994
DOI: 10.1080/10412905.1994.9698342
|View full text |Cite
|
Sign up to set email alerts
|

On the Genuineness of Citrus Essential Oils. Part XLIII. The Composition of the Volatile Fraction of Italian Sweet Orange Oils (Citrus sinensis(L.) Osbeck)

Abstract: Publication details, including instructions for authors and subscription information:ABSTRACT: The composition of the volatile fraction of Italian sweet orange oil obtained from blond and blood pulp fruits has been studied by GC and GC/MS. The study has been carried out on 190 genuine oils obtained by "Pelatrice" and "FMC in-line" industrial processing during the 1991-92 season. More than 55 components have been identified in the oil, with limonene (ca. 95%) as the main component. Because of the relatively hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…Results obtained for terpinen-4-ol and a-terpineol agree with those previously determined in our laboratory [11,12]. Results reported by Bicchi et al [12] for terpinen-4-ol ((+)/( -)-terpinen-4-ol = 38/62) are probably due to the analytical technique used: in fact, the determination of the enantiomeric distribution by gas chromatographic analysis of the whole oil can give peaks overlap that alter the results, mainly for those components present in small amounts.…”
Section: Cold-pressed Oilssupporting
confidence: 92%
See 1 more Smart Citation
“…Results obtained for terpinen-4-ol and a-terpineol agree with those previously determined in our laboratory [11,12]. Results reported by Bicchi et al [12] for terpinen-4-ol ((+)/( -)-terpinen-4-ol = 38/62) are probably due to the analytical technique used: in fact, the determination of the enantiomeric distribution by gas chromatographic analysis of the whole oil can give peaks overlap that alter the results, mainly for those components present in small amounts.…”
Section: Cold-pressed Oilssupporting
confidence: 92%
“…Values reported in the literature for the enantiomeric distribution of linalol in cold-pressed lemon oil [11,12,22] are in the ranges found in this work. There are no papers in the literature that report the seasonal variation of the enantiomeric distribution of linalol.…”
Section: Cold-pressed Oilsmentioning
confidence: 71%
“…Aldehydes and alcohols were present about in the same amounts, accounting for a level more than 25 times higher than that of esters. As in earlier reviews on orange oils, 5,6,18,19 octanal and decanal were found in considerable amounts, 0.1% each.˛-anď -Sinensal were also detected in trace amounts. The ratio ofˇ-sinensal/˛-sinensal was 1.8, which is similar to that of Ovale and Valencia late oils from Italy and Valencia late sweet orange oil from the USA.…”
Section: Orangementioning
confidence: 78%
“…17 Alcohols have been described to be most important to orange flavour, 5,20 and linalool was predominant among them. 5,18 In this study the contents of linalool and˛-terpineol were 0.4% and 0.1%, respectively. Terpinen-4-ol,ˇ-citronellol, geraniol, perilla alcohol andˇ-elemol were detected in trace amounts.…”
Section: Orangementioning
confidence: 96%
“…Progress in material technology has enabled the construction of mechanical valves with miniaturized connections, and bitter orange oils. 57,58 Multiple fraction LC-GC analysis was applied to neroli and petitgrain oils (hydrocarbons and oxygenated components) 59,60 and to bergamot essential oil. 61 In this last research, four LC fractions of increasing polarity were subjected to secondary GC analysis.…”
Section: Multidimensional Gas Chromatography (Gc-gc)mentioning
confidence: 99%